Non coronary lesions detected on multi-detector row cardiac computed tomography in patients with atypical chest pain - Basahai, Izzat Abdulla Ali (2010)
The study aimed to report the prevalence of non-coronary lesions detected on Cardiac MDCT angiography in patients with atypical chest pain. The prevalence of atypical symptoms for the study group and the association between the detected non coronary lesions and atypical symptoms were also reported A total of 123 patients underwent cardiac MDCT in Adventist hospital , Penang . from May 2005 until November 2009. Images were reviewed by two radiologists who were blinded to the clinical findings. Images were reviewed in four different CT windows and non coronary lesions were observed and recorded. The presenting symptoms were also noted for all those patients. Non coronary lesions were found in 91 (73.9%) patients . Of these extra-coronary lesions 5 (4.1%) were significant and required further follow up and evaluation while the rest were not significant and can be considered benign findings with no need for further evaluation. Lung lesions were seen in 81(65.8%) patients, cardiac abnormalities in 1(0.8%) patient, vascular abnormalities in 24(19.5%) patients, mediastinal lymph nodes in 33(26.8%) patients, esophageal abnormalities in 1(0.8%) patient, liver abnormalities in 49(39.8%) patients, splenic lesions in 11(8.9%) patients, bone abnormalities in 5(4.1%) patients and other abnormalities in 7(5.7%) patients. In the study group 33(26.8%) patients were scanned due to pain in the arms, epigastrium, shoulder or in the neck and the rest were scanned for screening. Of these 33 patients 5(4.1%) patients had lung bulla , interstitial lung changes were seen in 5(4.1%) patients, hepatomegaly were seen 11(8.9%) patients and in 4(3.3%) patients with other findings. Our study supports several other studies that highlighted the importance of careful reviewing of the non cardiac structures that was scanned with the heart and trained cardiologist. Any significant non coronary lesions must be reported and followed psychological and economic burdens on the patients. xvii up if necessary under clear and specific guidelines . Non siginificant coronary lesions need coronary arteries as part of cardiac MDCT angiography , preferably by a radiologist or no follow up and should not require further investigations that may put more psychological and economic burdens on the patients.